Spitzer microlensing parallax reveals two isolated stars in the galactic bulge - Zang, Weicheng; Tsapras, Yiannis; Gould, Andrew; Hundertmark, Markus; Mancini, Luigi (The astrophysical journal, 2020)
We report the mass and distance measurements of two single-lens events from the 2017 Spitzer microlensing campaign. The ground-based observations yield the detection of finite-source effects, and the microlens parallaxes are derived from the joint analysis of ground-based observations and Spitzer observations. We find that the lens of OGLE-2017-BLG-1254 is a 0.60 ± 0.03 M ⊙ star with D LS = 0.53 ± 0.11 kpc, where D LS is the distance between the lens and the source. The second event, OGLE-2017-BLG-1161, is subject to the known satellite parallax degeneracy, and thus is either a star with D LS = 0.40 ± 0.12 kpc or a star with D LS = 0.53 ± 0.19 kpc. Both of the lenses are therefore isolated stars in the Galactic bulge. By comparing the mass and distance distributions of the eight published Spitzer finite-source events with the expectations from a Galactic model, we find that the Spitzer sample is in agreement with the probability of finite-source effects occurring in single-lens events.
Gesehen am 12.11.2020